2020
DOI: 10.1177/1010539520965032
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Abuse Among Nurses Working in a Nepalese Government Hospital

Abstract: Verbal abuse among nurses is the most prevailing type of violence encountered by nurses. A cross-sectional research design was used to identify the characteristics of verbal abuse among nurses. A self-administered questionnaire was completed by 201 nurses working in a government hospital of Nepal. Nurses were exposed to verbal abuse and yelling or raising voice in an angry fashion was the most common forms experienced by 96.5% of the respondents. Patient’s relatives were reported as the main source of verbal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…They saw calling as a historical concept and experienced that as people still perceive nursing as a ‘calling profession’, it has led to exploitation of nurses. Recent studies have shown that nurses have described disrespect from their organizations and society, such as belittling comments, commands (Laminchhane & Bae, 2020), empty promises (Donahue, 2020) and comments on social media. Low salaries have been seen as discrimination and nurses have stated that one reason for this has been that people assume that nurses enter the profession because they have a calling for it (England, 2005; van der Cingel & Brouwer, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They saw calling as a historical concept and experienced that as people still perceive nursing as a ‘calling profession’, it has led to exploitation of nurses. Recent studies have shown that nurses have described disrespect from their organizations and society, such as belittling comments, commands (Laminchhane & Bae, 2020), empty promises (Donahue, 2020) and comments on social media. Low salaries have been seen as discrimination and nurses have stated that one reason for this has been that people assume that nurses enter the profession because they have a calling for it (England, 2005; van der Cingel & Brouwer, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a sense of mission enables nurses to have a more positive psychological state, thus arousing their enthusiasm for career success. However, some studies show that although the sense of mission provides multi-dimensional bene ts, it also poses great challenges [30] The existence of a sense of mission makes people think that nurses enter this profession because they have this demand [31]so as to be disrespected by organizations and society [32]and low wages. Therefore, it is very important to explore nurses' sense of mission in a broad and fair way and realize its complex in uence on nursing specialty.…”
Section: Introductionmentioning
confidence: 99%